Cognition of cancer among married women in Aguata L.G.A of Anambra State: The need to include therapeutic physical exercises in the management - Orajekwe, Veronica Ngozi (PT. Pena Produktif Kreatif, 2025)
Cancer is a disease caused by an uncontrolled division of abnormal cells in a part of the body. An evil or destructive practice or phenomenon that is hard to contain or eradicate. Some people describe it as “deadly” while others call it a “monster” it is a disease that cancer experts are still struggling to find a cure for. The purpose of the study was to determine the influence which location has on married women in Aguata L.G.A based on their level of cognition of cancer disease. In line with the objectives of the study two (2) research questions and one null hypotheses were postulated. Related literature were reviewed and summarized. Descriptive survey design was used with a population of 6000 married women. The sample for the study consisted 420 that was drawn by multi stage sampling combined with cluster, purposive and simple random sampling techniques. The instrument for data collection was self-developed questions. It was validated by two experts in Health and Physical Education and reliability correlation coefficient of 0.87 was calculated using Pearson Product Moment (PPM). The descriptive statistics of simple percentage and mean (x) scores were used to answer the research questions and the inferential statistics of chi-square (X2) was used to analyse one null hypothesis. Consequent upon the results got, the researchers rejected the null hypothesis which stated that there is no significant difference (p less than 0.05) between rural and urban marriage women in Aguata L.G.A. based on their level of cognition of cancer disease. Based on the findings recommendations were made pertinent among which is very urgent need of mass media campaign on what should be done by our married women to avoid this disease called cancer.